Keeping the doctor in the loop: Ayurvedic pharmaceuticals in Kerala. Issue 3 (1st September 2016) - Kudlu, Chithprabha
ABSTRACT: Ethnographic inquiry into Ayurvedic commodification in Kerala revealed the prevalence of a distinct regional pharmaceutical market dominated by physician-manufacturers, oriented towards supplying classical medicines to Ayurvedic doctors. This stands in sharp contrast to mainstream Ayurveda that is observed to have undergone biomedicalization and pharmaceuticalization. This paper argues that Kerala's classical-medicine-centric pharmaceutical market constitutes an alternative modernity because it provided Kerala Ayurveda with a different route to modernization impervious to the biomedical regime, as well as endowing it with the institutional power to safeguard its regional identity. Although physician-entrepreneurs are its key architects, it is sustained by value regimes shaped by a unique regional medico-cultural milieu. Even when industrially produced, classical medicines remain embedded within Ayurveda's socio-technical network; unlike proprietary drugs sold as individual product-identities through non-Ayurvedic channels, they travel together as a pharmacopeia, distributed through exclusive doctor-mediated agencies. This clinic-centric distribution format is best conceptualized as an open-source business model as it made low-margin generics viable by packaging them with therapies and services. Besides ensuring better access and affordability, it provided resistance to pharmaceuticalization and intellectual property concentration. By keeping the doctor in the loop, it prevented medicines from degenerating into de-contextualized commodities; the service component of Ayurveda therein preserved went on become the unique selling point in the health-tourism market. The tourism-inspired proliferation of Brand Kerala eventually triggered a paradigm shift in mainstream Ayurveda – shifting focus from 'pharmaceuticals' to 'services' and from 'illness' to 'wellness'. Furthermore, interacting with hybrid Ayurvedas in transnational markets, Kerala Ayurveda co-produces new alterities countervailing the structurally dominant biomedical paradigm.